2002
DOI: 10.1007/s004670200004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diabetic nephropathy: role of inducible nitric oxide synthase

Abstract: Nitric oxide (NO) is a multifunctional mediator that has been implicated in the short-term hemodynamic alterations that occur in acute streptozocin (STZ)-induced diabetes. We investigated the role of NO produced by inducible nitric oxide synthase (iNOS) in chronic STZ diabetic nephropathy. Diabetes was induced in C57BL/6 and iNOS knockout (KO) mice with two intraperitoneal injections of STZ, 100 mg/kg. Animals were maintained without insulin treatment for 40 weeks. There were no significant differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 39 publications
3
43
0
1
Order By: Relevance
“…Moreover, PDGF (B-chain) and its receptor appear to be highly expressed in mesangial and visceral epithelial cells and might play a role in the development of diabetic nephropathy [49]. Also oxygen radicals/oxidative stress may play a role in matrix accumulation in diabetic nephropathy [50,51]. Finally, aminoguanidine, an inhibitor of the formation of AGE but with antioxidant properties, attenuates diabetic nephropathy, which is consistent with a role of oxygen radicals in the pathogenesis of this disease.…”
Section: Glomerular Basement Membrane (Gbm)mentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, PDGF (B-chain) and its receptor appear to be highly expressed in mesangial and visceral epithelial cells and might play a role in the development of diabetic nephropathy [49]. Also oxygen radicals/oxidative stress may play a role in matrix accumulation in diabetic nephropathy [50,51]. Finally, aminoguanidine, an inhibitor of the formation of AGE but with antioxidant properties, attenuates diabetic nephropathy, which is consistent with a role of oxygen radicals in the pathogenesis of this disease.…”
Section: Glomerular Basement Membrane (Gbm)mentioning
confidence: 56%
“…A thickened tubular basement membrane is part of diabetic tubulo-interstitial disease, and represents a better indicator of diabetic nephropathy than GBM thickening [51,52]. Expression of transcription factor NF-κB in proximal tubular epithelial cells was strongly increased in diabetic patients with nephropathy and high urinary levels of AGE-albumin and carboxymethyl-lysine (CML).…”
Section: Tubular Basement Membranementioning
confidence: 99%
“…There are conflicting data on the role of iNOS in kidney injury in diabetes. Diabetes in iNOS knock-out mice was associated with worse renal injury as indicated by greater glomerular basement membrane thickening and worse tubule interstitial fibrosis, suggesting that iNOS is protective against diabetes-induced kidney injury (50). In contrast, kidney injury in streptozotocin-induced type 1 diabetes in rat was associated with an increase in iNOS expression, and sildenafil inhibited the iNOS increment and ameliorated kidney injury (51).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that reduced NO may contribute to susceptibility to injury and renal fibrosis (18,19). iNOS-derived NO modulates glomerulosclerosis and tubulointerstitial fibrosis in chronic streptozotocin nephropathy (17). This action is probably a result of the direct actions of NO on the synthesis and degradation of extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is a key mediator in renal physiology and pathology (17,18). Alterations of intrarenal NO synthesis play an important role in the pathogenesis and progression of diabetic complications (19).…”
mentioning
confidence: 99%